Molecular identification and functional characterization of the first Nα‐acetyltransferase in plastids by global acetylome profiling. Issue 14 (18th June 2015) - Dinh, Trinh V.; Bienvenut, Willy V.; Linster, Eric; Feldman‐Salit, Anna; Jung, Vincent A.; Meinnel, Thierry; Hell, Rüdiger; Giglione, Carmela; Wirtz, Markus; Van Damme, Petra; Gevaert, Kris
<x xml:space="preserve">Abstract</x> Protein Nα‐terminal acetylation represents one of the most abundant protein modifications of higher eukaryotes. In humans, six Nα‐acetyltransferases (Nats) are responsible for the acetylation of approximately 80% of the cytosolic proteins. N‐terminal protein acetylation has not been evidenced in organelles of metazoans, but in higher plants is a widespread modification not only in the cytosol but also in the chloroplast. In this study, we identify and characterize the first organellar‐localized Nat in eukaryotes. A primary sequence‐based search in Arabidopsis thaliana revealed seven putatively plastid‐localized Nats of which AT2G39000 (AtNAA70) showed the highest conservation of the acetyl‐CoA binding pocket. The chloroplastic localization of AtNAA70 was demonstrated by transient expression of AtNAA70:YFP in Arabidopsis mesophyll protoplasts. Homology modeling uncovered a significant conservation of tertiary structural elements between human HsNAA50 and AtNAA70. The in vivo acetylation activity of AtNAA70 was demonstrated on a number of distinct protein Nα‐termini with a newly established global acetylome profiling test after expression of AtNAA70 in E. coli. AtNAA70 predominately acetylated proteins starting with M, A, S and T, providing an explanation for most protein N‐termini acetylation events found in chloroplasts. Like HsNAA50, AtNAA70 displays Nε‐acetyltransferase activity on three internal lysine residues. All MS data have been deposited in the ProteomeXchange with identifier PXD001947 (http://proteomecentral.proteomexchange.org/dataset/PXD001947).